Irrigation system for oil palm in Colombia - an internet of things approach (2017)
In this article, we show a prototype of an irrigation system for oil palm plantations in Colombia. We make use of a predictive control model to improve the irrigation schedule. This model takes weather predictions from the Internet and uses them in the control model as a new variable to take into account when it comes to deciding whether the crops should be irrigated or not. A soil moisture sensor is used to both validate if the decision was correct and maintain the crop within the desired range of soil moisture. With this work, we want to give farmers the opportunity to embrace the Internet of Things (IoT) as a technology that can make their job easier and with better productivity in their plantations. © 2017, Springer International Publishing AG.